Czy uzasadniony jest postulat uwzględnienia specyfiki nauk humanistycznych i społecznych przy ocenie jednostek naukowych i badaczy? Między peer review a bibliometrią i naukometrią - Brzeziński, Jerzy Marian (Człowiek i Społeczeństwo, 2015)
Jerzy Marian Brzeziński, Czy uzasadniony jest postulat uwzględnienia specyfiki nauk humanistycznych i społecznych przy ocenie jednostek naukowych i badaczy? Między peer review a bibliometrią i naukometrią [Is the postulate to take into account the specificity of the humanities and social sciences during the evaluation of scientific units and researchers justified? From peer review to bibliometrics and scientometrics], edited by Z. Drozdowicz, S. Sztajer, „Człowiek i Społeczeństwo”, vol. XXXIX, Poznań 2015, pp. 9-30. Adam Mickiewicz University Press. ISBN 978-83-232-2953-7, ISSN 0239-3271. A significant element of institutional functioning of science is evaluating the functioning of scientific units (university faculties, research institutes) by institutions established by the state. In Poland such an evaluating body is The Committee for Evaluation of Scientific Units, which by means of standardised procedures – using a four-point scale (+A, A, B, C) – assesses scientific units every four years. The author considers the question: Should there be different criteria for evaluating scientific units conducting research in the field of the humanities and social sciences from those used in the field of science? In the author’s view, in order to obtain valid and reliable evaluation it is necessary to take into account the specificity of the humanities and social sciences.